Evaluasi Implementasi Program PANDAWA pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Pasaman Barat - Alifya , Falina; Ariany, Ria; Putera, Roni Ekha (Journal of Social and Policy Issues, 2024)
The PANDAWA program is a public service policy innovation at the West Pasaman Regency Population and Civil Registry Service. This program was created as a solution to limited access and the long distance people travel to get public services to the Disdukcapil office. This research aims to evaluate the implementation process of the PANDAWA Program at the West Pasaman Regency Dukcapil Office. This research uses qualitative methods by prioritizing primary data from interviews with informants, with the application of George C. Edward III's theory. Data collection techniques use interviews and observation. The research results show (1) communication: transition, clarity of information and consistency is implemented effectively. (2) disposition shows an attitude of commitment and meets expectations (3) The bureaucratic structure has clear SOPs and fragmentation. (4) Resources include staff who still need personnel who have an IT or computer educational background that is linear with the program, for facilities such as computers, additional procurement of better quality is necessary. Lastly, for network facilities disdukcapil must apply for addtional network capacity to the west West Pasaman Communication and Information Services as an institution that facilitates internet networks for all West Pasaman Regency local government organization. So that with this innovation we can create excellent services for the community.